Berndlehmannite: A new V-bearing sulfide mineral from the black shale-hosted Zhongcun vanadium deposit, South China - Fu, Xuerui; Li, Guowu; Xu, Lingang; Xue, Yuan; Sun, Ningyue; Hao, Jinhua; Jian, Wei; Yan, Hao; Ye, Huishou; Ding, Jianhua; Yuan, Peng (The American mineralogist, 2025)
Berndlehmannite, Cu(CrV)S4, is a newly identified V-bearing sulfide mineral discovered in the black shale-hosted Zhongcun vanadium deposit, South China. It is abundant in a phosphatic nodule-rich layer and is commonly mineralogically associated with roscoelite, quartz, and framboidal pyrite. Berndlehmannite exhibits black color in hand specimens with a black streak and it comprises subhedral grains that vary in size from 20 to 120 μm. The mineral is opaque with a cream-colored polished surface under reflected light. It has a Mohs hardness of 3½ with a {111} perfect cleavage, and its calculated density is 4.17 g·cm−3. Berndlehmannite is cubic, with space group Fd-3m; the unit-cell parameters determined from powder data are a = 9.8585(22) Å, V = 958.1(6) Å3, and Z = 8. The unit-cell parameters by single-crystal X-ray diffraction are a = 9.8374(2) Å, V = 952.01(6) Å3, Z = 8, and the final value of R is 0.015. The mineral is a member of the carrollite subgroup within the thiospinel group, featuring (Cr,V)S6 in octahedral coordination and CuS4 in tetrahedral coordination. The calculated empirical formula from electron-probe microanalysis is (Cu+0.99Zn0.02)Σ1.01(Cr3+0.87V4+1.00Sb0.07As0.04)Σ1.98S4.01 with an average V content of 17.0 wt%. It has the highest V component compared to other V-bearing minerals in black shales and may provide new insight into the vanadium enrichment mechanism in black shales. Berndlehmannite is named to honor Bernd Lehmann (1950- ), Professor emeritus of Economic Geology at Technische Universität Clausthal, Germany.